SANCTIONS AS AN INCENTIVE FOR FORMATION OF THE IMPORT SUBSTITUTION POLICY OF RUSSIA - Kuznetsova, Natalia; Kravchenko, Alla; Okonovenko, Ekaterina (Revista Inclusiones, 2020)
Nowadays, Russia is experiencing collective pressure in the form of economic sanctions from the United States and Western Europe. All taken sanctions were aimed at weakening the Russian economy and its maximum isolation. In such conditions, the problem of assessing the effectiveness of the sanctions policy is extremely urgent. The methodological approach for assessing the degree of effectiveness of economic sanctions in this research provides by three stages: determining the level of dependence of the Russian economy on international trade, assessing the level of development of the national economy, and assessing the policy of import substitution. Assessment of the relationship between GDP, exports and imports indicates about a high level of dependence of the Russian economy on international trade, except for the period 2008-2018. A comprehensive assessment of the competitiveness of the constituent entities of the Russian Federation demonstrates the negative development of the Russian economy.